Dietary considerations for the sick and hospitalized patients - Kumari, Shilpi; Vikram, M (Health Renaissance, 2017)
From a clinical perspective, knowledge of the nutritional status of a hospitalized patient is an indispensable strategy for establishing an adequate approach to the maintenance and/or recovery of nutritional status during the hospital stay. Nutritional status has an important impact on the course of underlying diseases. Malnutrition increases the rate of morbidity, length of hospital stay and certain other complications. Therefore malnutrition becomes very common among hospitalized patients which in turn lead to morbidity and increased hospital stay. Nutritional requirement of the patient vary in different disease condition and their mode of feeding depends upon the condition of the patient and the functioning organ Health Renaissance 2015;13 (1):